2003
DOI: 10.1029/2002gl016136
|View full text |Cite
|
Sign up to set email alerts
|

Cluster observation of a bifurcated current sheet

Abstract: The current sheet structure and motion at XGSM = −19.5 RE, observed by Cluster/FGM during 1055–1107 UT on 29 August 2001, is examined. It is found that during the interval 1055–1102 UT the current sheet moves vertically up and down with a velocity of about 60 km/s. During this interval the current sheet has a bifurcated structure: electric current is concentrated in two sheets with an extended layer of weak nearly uniform magnetic field in between. In the interval 1103–1107 UT the current sheet moves slowly up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
186
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 160 publications
(216 citation statements)
references
References 13 publications
27
186
2
Order By: Relevance
“…Karimbadi et al (2003) showed by full particle and hybrid simulations that the velocity shear, resulting from the presence of secondary ion population, drives the ion-ion kink (IIK) mode instability, which produces B x variations similar to the observed, and a displacement of the current peak from the sheet center to lobes. The calculated wavelength (2.8 R E ) and period (90 s) are close to the values which were found by Runov et al (2003) and Sergeev et al (2003).…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…Karimbadi et al (2003) showed by full particle and hybrid simulations that the velocity shear, resulting from the presence of secondary ion population, drives the ion-ion kink (IIK) mode instability, which produces B x variations similar to the observed, and a displacement of the current peak from the sheet center to lobes. The calculated wavelength (2.8 R E ) and period (90 s) are close to the values which were found by Runov et al (2003) and Sergeev et al (2003).…”
Section: Discussionsupporting
confidence: 68%
“…4) show that the current density is larger near the current sheet-lobe boundary than in the centre (B x =0). As was shown by Runov et al (2003) the current sheet has a bifurcated structure with off-center maximum of the vertical gradient of the magnetic field during this interval. It was also found that the set of B x variations during interval C is caused by waves propagating in the +Y direction polarized in Y −Z plane.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations